The novel TLR-9 agonist QbG10 shows clinical efficacy in persistent allergic asthma. - Beeh, K; Kanniess, F; Wagner, F; Schilder, C; Naudts, I; Hammann-Haenni, A; Willers, J; Stocker, H; Mueller, P; Bachmann, M; Renner, W (2013)
BACKGROUND: Allergen-specific TH2 responses contribute to the development of allergic asthma. Their increase may be due to a reduced early exposure to environmental pathogens, which induces a TH1 response, and thereby suppresses the allergic TH2 response. QbG10 (bacteriophage Qbeta-derived virus-like particle with CpG-motif G10 inside), a novel Toll-like receptor 9 agonist packaged into virus-like particles, was designed to stimulate the immune system toward a TH1-mediated protective response. OBJECTIVE: We examined clinical efficacy, safety, and tolerability of QbG10 with patient-reported and objective clinical outcome parameters in patients with mild-to-moderate persistent allergic asthma. METHODS: In this proof-of-concept parallel-group, double-blind, randomized trial, 63 asthmatic patients followed conversion to a standardized inhaled steroid and were treated with 7 injections of either QbG10 or placebo. Incorporating a controlled steroid withdrawal, the effects on patient-reported (day- and nighttime asthma symptoms, salbutamol usage, and 7-item-Asthma Control Questionnaire scores) and objective clinical outcome measures (FEV1, fraction of exhaled nitric oxide, and blood eosinophils) were assessed over 12 weeks (ClinicalTrials.gov number, NCT00890734). RESULTS: All patient-reported parameters improved overall between week 0 and 12 in QbG10-treated patients (n = 33) despite steroid withdrawal, compared with deteriorations observed under placebo (n = 30, P < .05). At week 12, two thirds of the QbG10-treated patients had their asthma "well controlled" (Asthma Control Questionnaire score ≤0.75) compared with one third under placebo. FEV1 had worsened to a clinically significant extent in patients on placebo, while it remained stable in QbG10 patients. Adverse events were mostly injection site reactions occurring after QbG10 administration. CONCLUSION: Treatment with QbG10 may contribute to continued asthma control during steroid reduction in patients on moderate or high-dose inhaled steroids.